Range of metastrongylids (superfamily Metastrongyloidea) of public health and veterinary concern present in livers of the endemic lizard Gallotia galloti of Tenerife, Canary Islands, Spain - Elena Izquierdo-Rodriguez; Lucia Anettová; Kristýna Hrazdilová; Pilar Foronda; David Modrý (Parasites & Vectors, 2023)
Abstract Background Endemic lizards of the genus Gallotia are of high ecological value to the terrestrial ecosystem of the archipelago of the Canary Islands, being potent seed spreaders as well as an important component of the diet of other vertebrates. The endemic lizard Gallotia galloti in Tenerife has recently been reported to be a paratenic host of Angiostrongylus cantonensis, an invasive metastrongylid with zoonotic potential that is associated with rats as definitive hosts. However, microscopic examination of G. galloti tissue samples also revealed the presence of other metastrongylid larvae inside granulomas on the liver of this reptile. The aim of this study was to investigate the presence of helminths other than A. cantonensis in tissues of G. galloti from Tenerife. Methods A multiplex-nested PCR targeting the internal transcribed spacer 1 was designed that enabled the species-specific detection of A. cantonensis, Angiostrongylus vasorum, Aelurostrongylus abstrusus, Crenosoma striatum and Crenosoma vulpis. Liver samples from 39 G. galloti were analysed. Results Five metastrongylids were detected: A. cantonensis (15.4% of samples analysed), A. vasorum (5.1%), Ae. abstrusus (30.8%), C. striatum (30.8%) and undetermined metastrongylid sequences (12.8%). Co-infection was highly prevalent among the lizards which tested positive. Conclusions The study provides a new specific tool for the simultaneous detection of a range of metastrongylids of veterinary importance as well as new data on the circulation of metastrongylids in an ecosystem dominated by lizards. Graphical Abstract